Exploring nudging strategies for plant-based dietary choices in hospital patients: a quasi-experimental study - Kristin Hünninghaus; Hannah Caroline Schäfer; Maik Plonka; Rebeca Montejano Vallejo; Gustav Dobos; Heidemarie Haller (International Journal of Behavioral Nutrition and Physical Activity)
Abstract Background The global food system is responsible for climate change, biodiversity loss, and land-use changes. At the same time, the prevalence of diet-related, chronic diseases is increasing worldwide. A dietary shift to a plant-based diet could protect both planetary and individual health. Nudging can positively influence dietary choices. We investigated how different nudges influenced inpatients’ choices of plant-based menus. Methods A quasi-experimental study was conducted across three consecutive four-week phases at the University Hospital Essen, Germany. In the baseline phase, inpatients chose meals from a standard menu without any intervention. In a second phase, an order nudge was applied by listing the plant-based dish first on the menu. In the third phase, a combined nudge was applied, adding a verbal recommendation to the order nudge. Data from 6,575 inpatients (mean age: 57.3 ± 18.7; 50.6% female) covering 26,949 meal choices were analyzed using logistic regression and generalized linear modeling. Results Independent of nudging, female sex and younger age predicted plant-based menu choices (p <. 001, respectively). Controlling for the effects of sex and age, patients were nearly twice as likely to choose the plant-based menu during both intervention phases compared to baseline (order nudge: OR = 1.95; 95% CI [1.55–2.45]; p <.001; combined nudge: OR = 1.95; 95% CI, [1.56–2.44]; p <.001). However, there was no significant difference in plant-based menu selection between the two nudges (OR = 1.00; 95% CI [0.80–1.25]; p =.992). Subgroup analyses further revealed that both women and men as well as middle-aged (36–64 years) and older adults (≥ 65 years), but not younger adults (18–35), were significantly more likely to select plant-based menus during the interventions compared to baseline. Among both sexes and across all age groups, no differences in plant-based meal selection were found between the order and the combined nudge (all p >.001). Conclusion Centrally implemented nudging is a simple and effective strategy that can increase patients’ choice of plant-based menus, which in turn may promote patient health and contribute to positive environmental outcomes. Trial registration DRKS00036763. Registered 29 April 2025.